Ensuring Renewable Energy Consumption through Innovation, R&D and Energy Import in Indonesia: A Time series Analysis - Purwanto, S. K.; Sinaga, Obsatar; Sidik, Morni Hayati Jaafar (International Journal of Energy Economics and Policy, 2020)
Energy resources have now been scarce as the use of energy resources has been increased. There is a need to manage the resources as in Indonesia there has been depletion of these resources accordingly and for this there has been a proposed solution which is to go for the renewable energy resources and energy consumption. Therefore, this research sets the propositions as how factors like innovation, resource development and the imports of energy can help ensure renewable energy consumption in Indonesia for the period of 1995-2019. The independent variables for research are innovation, research & development, and energy import. The dependent variable is renewable energy consumption and the control variables are population growth and energy consumption. The analysis is obtained by using Augmented Dickey Fuller (ADF), unit root tests, co-integration tests and Autoregressive distributed time lag (ARDL) models to understand the effect in chosen time period. The results indicate that innovation, research and development have a significant impact on renewable energy consumption. However, energy import has not been significantly impacting in the short run. The research proposes significant implications for policy makers to make effective policies for R & D and for the companies to go for innovation as to use renewable energy. Keywords: Renewable energy consumption, innovation, research & development, energy import, ARDL, Indonesia JEL Classifications: O13, B17 DOI: https://doi.org/10.32479/ijeep.10715